COVID-19 and Routine Childhood and Adolescent Immunizations: Evidence from Louisiana Medicaid. Issue 6 (7th February 2022) - Walker, Brigham; Anderson, Andrew; Stoecker, Charles; Shao, Yixue; LaVeist, Thomas A.; Callison, Kevin
Highlights: We compared vaccine use in 2020 with use in prior years in Louisiana Medicaid. Vaccination rates were lower in spring and late summer when back-to-school care occurs. We found total reductions of 28% in MMR, 35% in HPV, and 30% in Tdap vaccinations. There was little evidence of vaccine use recovery in later months. Poor children and adolescents in 2020 were more vulnerable to preventable infections. Abstract: The COVID-19 pandemic disrupted routine vaccinations for children and adolescents. However, it remains unclear whether the impact has been different for children and adolescents from low-income families. To address this, we compared monthly routine vaccination use per 1000 vaccine-eligible children and adolescents enrolled in Louisiana Medicaid in the years before (2017–2019) and during the COVID-19 pandemic (2020). Compared to the 2017–2019 average vaccination rates, we found a 28% reduction in measles, mumps, and rubella (MMR), a 35% reduction in human papillomavirus (HPV), and a 30% reduction in tetanus, diphtheria, pertussis (Tdap) vaccinations in 2020. Vaccine uptake was lower in April 2020 after the declaration of a state of emergency and in late summer when back-to-school vaccinations ordinarily occur. We found little evidence of recovery in later months. Our findings suggest that a substantial number of disadvantaged children may experience longer periods of vulnerability to preventable infections because of missed vaccinations.